Evaluation of validation of Anderson score for diagnosis of acute appendicitis by histopathology - Goel, Kanwar Singh; Goel, Sapna (International Surgery Journal, 2018)
Background: Appendicectomy is a very common operation performed. Removing normal appendix leads to multiphasic problems. Furthermore, appendix has proved to be a useful structure in reconstructive surgeries. We are going to evaluate validation of Anderson score for diagnosis of acute appendicitis and confirm the result by histopathology. Methods: This prospective observational study was performed in Surgery Department in SGT Medical College, Gurugram, Haryana. Total patients were 100. A detailed history was taken, clinical examination and investigations were done. All patients were subjected to Anderson score. Patients were operated. Appendix was sent for Histopathology examination. Analysis of the data was done by SPSS software version 23. Sensitivity, specificity, positive predictive value and negative predictive values were found out. Chi square test was duly applied. Results: In 70 patients, Anderson score was >8, was in favour of acute appendicitis. It means these patients should require surgery. In 30 patients score was <8. Most common histopathology finding was acute appendicitis then diffuse suppurative appendicitis followed by gangrenous appendicitis still followed by diffuse suppurative appendicitis with peri appendicitis. Conclusions: we have found out that if Anderson score is ≥8, appendicectomy should be done. But if Anderson score is <8, as per Anderson scoring system, appendicectomy should not be done, but we should not go by this. We should review the patient, further investigations should be carried out, senior surgeon’s opinion should be taken, and then final decision should be taken.